Transportation Mode Choice and Sustainability: A Study of Tourist Transportation in The National Tourism Strategic Area Ciwidey - Umar Fariz; Nahry; Gloriani Christin (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2024)
This study conducted in Bandung Regency delves into the factors influencing the choice of transportation modes for tourists and provides practical insights. Specifically, the research examines the influence of park-and-ride security, travel time savings, and travel costs on the selection of private vehicles and shuttle buses. The findings emphasize the importance of sustainable transportation facilities and efficient public transport services, offering a practical roadmap for addressing transportation needs for tourists in Bandung Regency. With a focus on the park-and-ride concept, this research identifies and analyzes the factors influencing mode choice between private vehicles and public transportation. The study was conducted in Ciwidey, a natural tourism area in Bandung Regency, which offers diverse attractions such as nature-based tourism, ancient sites, culinary experiences, and water tourism. The findings of this research aim to contribute to the improvement of sustainable transportation and mobility choices for tourists while alleviating traffic congestion and environmental impact in Bandung Regency's tourism areas.